Across-frequency behavioral estimates of the contribution of inner and outer hair cell dysfunction to individualized audiometric loss - Johannesen, Peter T.; Pérez-González, Patricia; Lopez-Poveda, Enrique A. (Frontiers in Neuroscience, 2014)
Identifying the multiple contributors to the audiometric loss of a hearing impaired (HI) listener at a particular frequency is becoming gradually more useful as new treatments are developed. Here, we infer the contribution of inner (IHC) and outer hair cell (OHC) dysfunction to the total audiometric loss in a sample of 68 hearing aid candidates with mild-to-severe sensorineural hearing loss, and for test frequencies of 0.5, 1, 2, 4, and 6 kHz. It was assumed that the audiometric loss (HLTOTAL) at each test frequency was due to a combination of cochlear gain loss, or OHC dysfunction (HLOHC), and inefficient IHC processes (HLIHC), all of them in decibels. HLOHC and HLIHC were estimated from cochlear I/O curves inferred psychoacoustically using the temporal masking curve (TMC) method. 325 I/O curves were measured and 59% of them showed a compression threshold (CT). The analysis of these I/O curves suggests that (1) HLOHC and HLIHC account on average for 60–70 and 30–40% of HLTOTAL, respectively; (2) these percentages are roughly constant across frequencies; (3) across-listener variability is large; (4) residual cochlear gain is negatively correlated with hearing loss while residual compression is not correlated with hearing loss. Altogether, the present results support the conclusions from earlier studies and extend them to a wider range of test frequencies and hearing-loss ranges. Twenty-four percent of I/O curves were linear and suggested total cochlear gain loss. The number of linear I/O curves increased gradually with increasing frequency. The remaining 17% I/O curves suggested audiometric losses due mostly to IHC dysfunction and were more frequent at low (≤1 kHz) than at high frequencies. It is argued that in a majority of listeners, hearing loss is due to a common mechanism that concomitantly alters IHC and OHC function and that IHC processes may be more labile in the apex than in the base.